Analisis Teknikal Harga Saham Waskita Karya Tahun 2017 dengan Metode ARIMA - Windasari, Wahyuni (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
As an investor needs to do an analysis before making a decision either in selling or buying shares. Security analysis consist of two types of analysis, namely tecnical analysis and fundamental analysis. Technical analysis to test wheater historical data will predict stock prices as a consideration to buy or sell an investment's instrument. One type of technical analysis is the ARIMA method. In this research uses daily stock price of WSKT Tbk during 1 Januari–10 Oktober 2017 to predict stock prices the few days. The best ARIMA model to describe WSKT stock price movement is MA(4), with MAE predict data is 480.25.Key words : forecasting, ARIMA, technical analysis, stock prices.